2020
DOI: 10.1186/s40463-020-00462-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined application of single-energy metal artifact reduction and reconstruction techniques in patients with Cochlear implants

Abstract: Background The purpose of this study was to develop an effective method of reducing metal artifacts in cochlear implant (CI) electrodes. Methods The temporal bones of 30 patients (34 ears) after CI were examined with 320-detector row computed tomography, which was evaluated by two senior radiologists using a double-blind method. Noise, artifact index, signal-to-noise ratio, and the subjective image quality score were compared before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…7 However, their method used for coregistration of the pre-and postoperative images was unique from the method used in our study. specifically, Skinner et al An additional option for metallic artifact reduction reported in the literature is the combined application of single energy metal artifact reduction and reconstruction techniques in patients with CIs that was shown to be conducive to accurate localization by Wei et al 18 The methods described in the article for this technique included adjusting the scan range according to the localization image to include the range of the entire CI. In a separate scanning mode, one layer was swept within the scanning range, and two regions of interest were set inside.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 However, their method used for coregistration of the pre-and postoperative images was unique from the method used in our study. specifically, Skinner et al An additional option for metallic artifact reduction reported in the literature is the combined application of single energy metal artifact reduction and reconstruction techniques in patients with CIs that was shown to be conducive to accurate localization by Wei et al 18 The methods described in the article for this technique included adjusting the scan range according to the localization image to include the range of the entire CI. In a separate scanning mode, one layer was swept within the scanning range, and two regions of interest were set inside.…”
Section: Resultsmentioning
confidence: 99%
“…An additional option for metallic artifact reduction reported in the literature is the combined application of single energy metal artifact reduction and reconstruction techniques in patients with CIs that was shown to be conducive to accurate localization by Wei et al 18 . The methods described in the article for this technique included adjusting the scan range according to the localization image to include the range of the entire CI.…”
Section: Discussionmentioning
confidence: 99%
“…AI is de ned not by the ratio of SDs in the metal artifact image and the background image, but by the difference between those of SDs [7][8][9][10]13]. Therefore, CT images with high image noise increase the difference between the SDs of the metal artifact image and the SDs of the background image.…”
Section: Objective Analysismentioning
confidence: 99%
“…The cause of metal artifacts are beamhardening, extensive photon starvation, and scatter [2]. Various methods are used to reduce metal artifacts, including alteration of image reconstruction method [3], scanning with a dual-energy CT [4,5], and using metal artifact reduction software [1,3,[5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation